2023
DOI: 10.3390/antibiotics12081327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enterococcal Probiotic Usage and Review of Potential Health Benefits, Safety, and Risk of Antibiotic-Resistant Strain Emergence

Eric Jeeho Im,
Harry Hyun-Yup Lee,
Minzae Kim
et al.

Abstract: Enterococci are often used in probiotics but can also cause nosocomial infections. As such, enterococcal consumption may have beneficial health effects, but a thorough evaluation of virulence absence and risk of antibiotic resistance spread is needed at the strain level. This article reviewed ten online health product shopping websites in the US. On these websites, 23 probiotic products using enterococci were found across 12 companies. In addition, this article reviewed studies that demonstrated the probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…However, also the release via membrane vesicles could be an explanation which is supported by vesicle releasing L. plantarum (Yu et al 2022). Interestingly, systematic analysis of the signal peptides and culture filtrates of different lactobacilli suggested that further bacterial species from the genera Lactobacillus, Akkermansia, and Enterococcus with described probiotic potential (Li et al 2024; Im et al 2023) release putative FPR2 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…However, also the release via membrane vesicles could be an explanation which is supported by vesicle releasing L. plantarum (Yu et al 2022). Interestingly, systematic analysis of the signal peptides and culture filtrates of different lactobacilli suggested that further bacterial species from the genera Lactobacillus, Akkermansia, and Enterococcus with described probiotic potential (Li et al 2024; Im et al 2023) release putative FPR2 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics and prebiotics can help alleviate symptoms associated with intestinal disorders such as IBD, IBS, and antibiotic-associated diarrhea [ 232 ]. They may reduce inflammation, promote regular bowel movements, and alleviate digestive discomfort [ 68 ]. The efficacy and specific benefits of probiotics, prebiotics, and symbiotics may vary depending on the individual, the specific strains or fibers used, and the dosage.…”
Section: Therapeutic Interventions Based On Probioticsmentioning
confidence: 99%
“…To meet the clinical requirements, EFSA (European Food Safety Authority), WHO, and FAO issued mandatory guidelines to probiotic researchers, stating that the strains must meet safety and functionality requirements, such as the route of strain selection, nonpathogenic, non-immunogenic nature, resistance to antibiotics, long durability in the gastrointestinal tract, and the ability to maintain their activity during production, processing, and preservation, which are crucial for patient safety [5,6]. The carriers or matrix employed in the formulation are also vital since they can impair the strain's viability, lowering the product's quality [7,8].…”
Section: Probiotic Strain Selection Criteria and Requirementsmentioning
confidence: 99%